MAPPING INNOVATION AND ENTREPRENEURIAL ECOSYSTEMS AT CITY LEVEL: : THE PROPOSITION OF A FRAMEWORK FOR ENGAGING ACTORS - Gazaro dos Santos, Diego Alex; Carneiro Zen, Aurora; Faccin, Kadigia; Anicet Bittencourt, Bruno; Franke Gonçalves, Leonardo (Sociedade e Território, 2025)
Entrepreneurial and innovation ecosystems (EIEs) in cities have been recognized as a critical force behind regional development. Hence, fostering EIEs has been a priority for the development of cities and drives significant policy and program activities. In this paper, we argue that mapping and engagement of quadruple helix actors, i.e. academia, companies, government, and society, is capable of guaranteeing collaboration and thus promoting innovation and entrepreneurship for cities. For this investigation, we collected indicators and employed the Action Research (AR) approach, alongside Design Thinking (DT), in five workshops in which 135 people form the quadruple helix in the EIE of Porto Alegre, Brazil. The indicators provided guidance for relevant issues, and the workshops encouraged multilateral collaboration between the actors. Thereby, we propose a five-step framework based on AR and DT to map EIEs and to improve collaboration of quadruple helix actor in the cities.